2021
DOI: 10.3390/cells10051196
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of CT-Based Imaging in Adipose Tissue and Coronary Inflammation

Abstract: A large body of evidence arising from recent randomized clinical trials demonstrate the association of vascular inflammatory mediators with coronary artery disease (CAD). Vascular inflammation localized in the coronary arteries leads to an increased risk of CAD-related events, and produces unique biological alterations to local cardiac adipose tissue depots. Coronary computed tomography angiography (CTA) provides a means of mapping inflammatory changes to both epicardial adipose tissue (EAT) and pericoronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 97 publications
(140 reference statements)
1
13
0
Order By: Relevance
“…Compared to other visceral depots, it has lower glucose utilization and also has brown fat properties that are hypothesized to protect the myocardium against hypothermia by producing free fatty acids [17] . Non-invasive imaging techniques can be used to measure adipose tissue as a surrogate marker of inflammation [19] . As the attenuation of inflamed adipocytes increases, inflamed cells can be distinguished from non-inflamed cells by CT-scan analyses based on the HU.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other visceral depots, it has lower glucose utilization and also has brown fat properties that are hypothesized to protect the myocardium against hypothermia by producing free fatty acids [17] . Non-invasive imaging techniques can be used to measure adipose tissue as a surrogate marker of inflammation [19] . As the attenuation of inflamed adipocytes increases, inflamed cells can be distinguished from non-inflamed cells by CT-scan analyses based on the HU.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the release / uptake of free fatty acids (FFAs), EAT plays an important role in CAD by supporting the efficiency of myocardial glucose utilization [ 13 , 14 ]. Clinically, the volume and thickness of EAT have been measured by cardiac magnetic resonance imaging (MRI), computed tomography (CT) [ 15 ], and echocardiography (echo) [ 16 ]. Several studies have shown that enlarged EAT is associated with the occurrence and development of CAD [ 17 ], which was later termed a potential predictor of the disease [ 16 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the “outside-to-inside” theory, even EAT inflammation may contribute to atherosclerosis through a process that begins in EAT and then propagates inward to the vasculature because adipokines and other fat-derived mediators elicit changes within the vessels [ 9 ]. Moreover, this relationship is not simply unidirectional, as emerging evidence suggests that mediators derived from the vessel wall affect distinct changes to adipose tissue on a local basis [ 10 ]. In particular, the nominal function of human adipose tissue becomes deranged under adverse cardiometabolic/stressful conditions, such as excessive energy supply, obesity, insulin resistance, and diabetes [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of PCAT on CT provides indirect quantification of coronary inflammation and could be emerging as a promising imaging implement in both stable and “vulnerable” populations. While standardized CT thresholds of inflammation are yet to be established, they present a powerful avenue to enhance primary prevention initiatives [ 10 ]. A new biomarker called “fat attenuation index (FAI)”, defined as the mean PCAT attenuation within a radial distance from the outer coronary artery wall equal to the average vessel diameter, was proposed.…”
Section: Introductionmentioning
confidence: 99%